Dataset of a de novo transcriptome assembly for the leaves and rhizomes of a five-year-old Atractylodes chinensisMendeley Data - Yelin Tian; Lizhi Ouyang; Xinyu Li; Li Xiao; Xu Qiao; Yixuan Chen; Tingting Fang; Yimian Ma (Data in Brief)
Atractylodes (A.) chinensis (DC.) Koidz. is a traditional Chinese medicinal plant. The rhizome contains its medicinal component, which consists of abundant essential oils. Sesquiterpene and atractylodin are the main active ingredients in these essential oils. On the other hand, the leaves contain less medicinal active ingredients. Thus far, studies on the formation mechanism of the active ingredients, especially atractylodin, are still limited. This study used RNA sequencing to reveal the de novo transcriptome of the leaves and rhizomes of a five-year old A. chinensis plant with divided leaves. High-throughput sequencing data was acquired using the Illumina NovaSeq X Plus system (Illumina, USA) in PE150 mode. After the data was corrected and filtered, the clean data was used for subsequent analysis. Based on the assembled sequence file, the differentially expressed unigenes between the rhizomes and leaves of A. chinensis were analyzed. The assembled unigene file and table including these differentially expressed unigenes was deposited in the “Mendeley Data” database. The raw SRA data was deposited in the National Center of Biotechnology Information (NCBI) Sequence Read Archive (SRA) database.